El método de las tres R´s ecológicas y la capacidad creativa en estudiantes del 4° grado de la institución educativa - Altamirano Quinto, Julio César (2020)
The research is aimed to determine the effectiveness of the Three R's ecological method in the development of creative capacity, of the students of the 4th grade of Primary Education, of the Educational Institution from Huancavelica. The research is an applied type, with an experimental level; it was used the scientific, logical, practical and statistical method; the design: the research with pre-test and post-test, with a single group. The sample: 20 students; for data collection was used the survey technique and the instrument, the Creative Imagination Test (CIT). At the end of the research, it is observed that the general level of creativity has a percentage of 0% of students who are at the low level; 0% of students are in the average level; 65% of students are in the high average level and, finally, 35% of students are in the high level. Conclusion: The method of the three ecological R's has a significant effect on the development of creative capacity.